The Effect of Problem Based Learning (PBL) Model on Students’ Speaking Achievement at Class XI Of SMAN 10 Kendari - Ismawati, Wa Ode; Rohmana, Rohmana; Siam, Siam (Journal of Teaching of English, 2021)
This research is conducted to find out whether there is a significant effect of Problem Based Learning (PBL) Model on students’ speaking achievement at class XI of SMAN 10 Kendari. The design of this research was pre-experimental research (one group pre-test and post-test design). The population involved the XI-graders science program (X1 MIA) of SMAN 10 Kendari which consisted of four classes, while the sample taken by using simple random sampling technique was students at class X1 MIA 4 consisting of 21 students. The instrument was an oral test about asking and giving opinion related to the topic. The researcher used Paired Sample T-test through SPSS 16.0 version to analyze the result of the research. The result showed that the mean score of students’ speaking achievement in posttest was higher than that of in pre-test (55.47 > 37.14). The hypothesis testing found that the value of sig (2 Tailed) was 0.00 while the significant alpha value was 0.05. It can be concluded that the value of Sig (2 Tailed) was lower than the significant alpha value (0.00 < 0.05). It means that the use of Problem Based Learning model has a significant effect on students’ speaking achievement at the XI grade of SMAN 10 Kendari.